Effects of increasing total sulfur amino acid:lysine ratio on growth performance of 25 to 50 lb pigs - M De La Llata; P R O'Quinn; J C Woodworth; S A Moser; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred and fifty pigs were used in a 27-d growth study to determine the appropriate total sulfur amino acid:lysine ratio for 25 to 50 lb pigs. Pigs were blocked by weight (initially 22.5 lb) and allotted to one of 10 treatments arranged in a 2 x 5 factorial with two levels of total dietary lysine (.95 and 1.250/0) and five total sulfur amino acid ratios (.45, .50, .55, .60, and .65% of total lysine). Increasing total lysine from .95 to 1.25% increased ADG and improved FIG. Increasing the total sulfur amino acid:lysine ratio did not affect ADG but improved F/G. These results indicate that the optimal total sulfur amino acid:lysine ratio for the 25 to 50 lb pig is not greater than 55%.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Methionine; Lysine; Nursery pigs